PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN) - Hasana, Nur; Anwar, Azwar; Ryketeng, Masdar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of liquidity and profitability on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. The independent variables in this study are liquidity measured by Current Ratio (CR) and profitability measured by Return On Asset (ROA), while the dependent variable is firm value measured by Price to Book Value (PBV). This study employed an inferential quantitative approach using secondary data obtained from company financial statements. The sampling technique used purposive sampling, resulting in 31 companies with a total of 155 observations over five years. Data analysis techniques included classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination test using SPSS version 26. The results showed that liquidity had a negative and significant effect on firm value with a significance value of 0.002 < 0.05. Profitability had a positive and significant effect on firm value with a significance value of 0.000 < 0.05. Simultaneously, liquidity and profitability had a positive and significant effect on firm value with a significance value of 0.000 < 0.05. The coefficient of determination test showed that liquidity and profitability were able to explain 37.1% of the variation in firm value, while the remaining 62.9% was influenced by other factors outside the study.